Impact of the use of seawater on acid mine drainage from mining wastes. (10th January 2023) - Texeira, Luiza; Calisaya-Azpilcueta, Daniel; Cruz, Constanza; Botero, Yesica L.; Cisternas, Luis A.
Abstract: The copper mining industry is vital in the transition to fossil-free power for achieving sustainability worldwide, which is mainly based on the exploitation of copper sulfide ores. However, the mineral processing produces a large volume of mine tailings, and their quantity is almost equal to the ores treated. Acid mine drainage (AMD) is a challenging environmental problem caused by tailing disposal when it is not well managed. In addition, several copper mining companies employ seawater in their process because they operate in arid or semi-arid regions, including northern Chile, southern Peru, and Australia. For copper sulfide mineral processing, the use of seawater is not a limitation in the flotation process, and positive and negative effects appear compared to using fresh water. However, there are no records in the literature on the impact of seawater on the generation of AMD, considering that it is a solution with a high concentration of different ions. This study aims to evaluate the chemical stability of synthetic tailings with and without seawater by kinetic tests using seven humidity cells. The synthetic tailings are mixtures of pyrite, chalcopyrite, arsenopyrite, and quartz. The main results show that the AMD generation kinetics after 25 weeks of testing humidity cells leached with distilled water (acid-generating cells) behaved differently than the humidity cells leached with seawater (non-acid-generating cells). After 25 weeks of testing, the acid-generating humidity cells had a pH value below 2.26, while the non-acid-generating humidity cells had a pH value above 7. It was also shown that fine-particle-size granulometry generates AMD faster than coarse-particle-size granulometry. Finally, the sulfide minerals' ion dissolution occurred when the humidity cells were leached with distilled water and not when leached with seawater. The results show that using non-desalinized seawater in copper ore processing can help prevent AMD due to the buffering effect of seawater and the protection coat formed by oxyhydroxide and/or bivalent cations. Highlights: Seawater's impact on AMD generation is studied using synthetic tailings. The synthetic tailings are mixtures of pyrite, chalcopyrite, arsenopyrite, and quartz. The main results show no AMD generation using seawater in the humidity cells test. From the point of view of tailing storage, seawater may protect against AMD in dry areas.